Approximating graphs of a class of general Sierpinski triangles and their normalized Laplacian spectra. (March 2021) - Zhu, Zhiyong
The normalized Laplacian spectrum of a graph is an important tool that one can use to find much information about its topological and structural characteristics and also on some relevant dynamical aspects, specifically in relation to random walks. In this paper we devise an essentially algorithm to obtain the approximating graphs of a class of general Sierpinski triangles and their normalized Laplacian spectra, and illustrate such algorithm by a quasi-program of Matlab. In the meantime, our work also enriches the graphs whose spectrum is known.